In vivo properties of the Drosophila inebriated-encoded neurotransmitter transporter. - Huang, Y.; Stern, M. (Journal of Neuroscience, 2002)
Altering neurotransmitter levels within the nervous system can cause profound changes in behavior and neuronal function. Neurotransmitter transporters play important roles in regulating neurotransmitter levels by performing neurotransmitter reuptake. It was previously shown that mutations in the Drosophila inebriated (ine)-encoded neurotransmitter transporter cause increased neuronal excitability. Here we report a further functional characterization of Ine. First we show that Ine functions in the short-term (time scale of minutes to a few hours) to regulate neuronal excitability. Second, we show that Ine is able to control excitability from either neurons or glia cells. Third, we show that overexpression of Ine reduces neuronal excitability. Overexpression phenotypes of ine include: delayed onset of long-term facilitation and increased failure rate of transmitter release at the larval neuromuscular junction, reduced amplitude of larval nerve compound action potentials, suppression of the leg-shaking behavior of mutants defective in the Shaker-encoded potassium channel, and temperature-sensitive paralysis. Each of these overexpression phenotypes closely resembles those of loss of function mutants in the para-encoded sodium channel. These data raise the possibility that Ine negatively regulates neuronal sodium channels, and thus that the substrate neurotransmitter of Ine positively regulates sodium channels.